Transpersonal Psychology: Array - Panfiloiu, Carmen (New Trends in Psychology, 2021)
A relatively new field of psychology, transpersonal psychology wants the scientific approach of the whole range of human experiences, which includes the pain of trauma and dysfunction on the one hand and the peaks of creativity, intuition and peak functioning on the other. Transpersonal psychology is a study of human growth and development. Psychologists who subscribe to transpersonal psychology believe that the continuum begins with people who lack the identity of the ego and are essentially the basis of the development structure of humanity. The affected psychotic personality and limit would fall into this category. As we move toward functionality, people with stronger equal states and concise and definitive object relationships are represented as “normal”. Moving further into human development are mystics and meditators who are seen as transcending the conscious state and identifying a supreme being, God or universal force.